(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
Does a space for regional autonomy exist in the field of biolaw? The relationship between state and regions, in the Italian Constitution, is traditionally defined as asymmetric regionalism. The aim of the paper is to investigate the extent of regional autonomy in the field of biolaw. After having reconsidered the fundamental steps of Constitutional Court’s interpretation of matters reserved to the exclusive competence of the state, the essay focuses on regional interventions, both on a legislative and on administrative levels. The results of the research show that, in the field of biolaw, the state holds a wide legislative power, which shall nevertheless be exercised in collaboration with regions. Moreover, the existence of a wide power of regions to organise their healthcare services has a relevant impact on the effectiveness of fundamental rights’ protection in biolaw matters. Finally, the paper tackles the path towards the regional achievement of further differentiation as provided by Art. 116 of the Constitution, which is considered as a concrete opportunity not only for the Regions that are undertaking the agreement with the state to this end, but for the Republic as a whole.